(3GbJWGa GdRgQ ef LhGfH CTLGQ GdfgQs - (3YHO GdeYWj Hf SGde Hf YeQ GdTHdj GdSedGhj,J (B1127 (3g` s ((3YHO Gddg GdMGL jhSa Hf GdTjN eMeO GdZQjH s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ YHO GdeYWi Hf SGde Hf YeQ GdTHdi GdSedGhi GdTGaYi gPg LedI eSGFd ef aJGhi GdTjN GdfHJjJi hZjQg hSejJgG GbJWGa GdRgQ ef LhGfH CTLGQ GdfgQ s
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdceGd SGFd Jhajb dMSf GdMGd Ke GdUdGI hGdSdGe CHOG Ydi GdfHi GdgGTei CMeOG JeJ HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B177s
Keywords: (3Gdabg GdTGaYjs